Kosakata yang mencerminkan Sistem Pengetahuan dan Teknologi Pertanian dalam Ranah Bercocok Tanam Padi pada Masyarakat Jawa: Sebuah Kajian Etnolinguistik - Nur’aini Wahyuningsih (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Anthropological linguistics (ethnolinguistics) is the study of correlations between language and cultures. Language cannot divide from social culture facts of its community. The Javanese very familiar with rice. In fact, Javanese identic as agraris people.This research is descriptive by work steps systematically are collecting data, clarifying data, analyzing and takes conclusion. The results of this research are (1) the lingual that uses in rice planting domain of Javanese consist of nouns and verbs; (2) based on the lingual was implied the Javanese knowledge on farming.